A formação profissional continuada e o ensino de geografia nos anos iniciais em uma perspectiva histórico-cultural - Moraes, Ismael Donizete Cardoso de (2022)
The continuing education of teachers has been constituted through multiple theoretical approaches and methodological paths. Specifically, in this work, theoretical-methodological aspects of the continuing education of pedagogues were addressed, considering the challenges to teach geography in the early years. Thus, the development of the research had as reference the continuing education of pedagogues, organized from the practical professional problems , from the cultural-historical theory and from the concepts of landscape, place, city and urban. In this sense, the research problem is how continuing education, imagined and thought from the practical professional problems, can help teachers in the early years to appropriate fundamental aspects of geography content and plan classes in a way that students go beyond the limits of classification and mechanical memorization of contents. Following this proposition, the general objective is to understand how continuing education focused on professional problems, based on historical-cultural theory, helps teachers to appropriate geographic and didacticmethodological concepts and develops a teaching proposal based on authorship and in the autonomy of teaching practice. To approach this objective, we specifically seek: to analyze the importance of continuing education for the development of geographical knowledge by pedagogues who work in the early years of Elementary School; identify and enhance the influence of the place and the landscape (of the city of Barra do Garças) in the teaching and study of geographical contents in the early years of Elementary School; verify the appropriation of knowledge and geographic thinking in the planning and development of the plan in the classroom; investigate the mediating processes in the elaboration and execution of the teaching proposal. Thus, the methodology has primacy in the qualitative aspects parameterized by the collaborative attributes of action research. Based on this perspective, observation, narratives and plans developed by the teachers are used as investigation procedures. The study of the concepts of place, landscape, city and urban, organized from the problematization, systematization and synthesis, didactic steps developed by Cavalcanti, and the elements of didactic mediation of Davydov, from the general to the particular, from the collective to the individual, and from the empirical to the theoretical-conceptual, they are essential in the development of research. The results point to an advance in the domain of concept s, perceptible in the teachers’ speeches, in the narratives, in the plans re-elaborated during the course and in the development of the plan in the classroom by one of the teachers. In the re-elaborated plans and in the didactic action, it is possible to perceive an advance in the harmony between the concepts of landscape and place with the objectives and contents. Also, the relationship between the concepts of place and landscape with the concepts of urban and city became more evident, as well as the elements of didactic mediation of geographic contents.